Six Weeks of Hiit Based on Repeated 5-Meter Sprints Vs. Countermovement Jumps: Effects on Physical Performance Among Karate Athletes. a Pilot-Study - Herrera-Valenzuela, T (Idokan Poland Association, 2020)
Background. The kumite section or karate kumite is characterized by high-intensity activity, including explosive actions. Problem and Aim. Determine the magnitude of the effect on the physical performance of karate athletes of the application of two protocols: HIIT-SPRINT and HIIT-JUMP performed at the beginning of a training session (20 minutes) for six weeks. Methods. Both the HIIT-JUMP and HIIT-SPRINT group underwent a six-week HIIT program, while the CONTROL group continued with their regular karate training. The athletes performed the following tests: squat jump, countermovement jump, 5m and 10m line speed, change of direction, aerobic capacity and body composition. Results. Fat mass (kg) decreased in the HIIT-JUMP group (ES =-0.63), while the HIIT-SPRINT group reduced the percent of body fat (ES =-0.85). Jump height for the squat and countermovement jumps increased in the HIIT-SPRINT group (ES = 0.82 and 0.94, respectively) and 10-m test (ES =-1.14) and change in direction (ES =-0.60) times were reduced. The HIIT-JUMP group decreased their times for the 5-m and 10-m tests (ES =-0.97 and-1.07, respectively). The HIIT SPRINT group improved in the 5-m test compared to the CONTROL group (ES = 0.62). Conclusions. These results suggest that both HIIT modalities offer specific adaptations, and could be considered as complementary to the training of athletes. © 2020 Idokan Poland Association.